2004
DOI: 10.1292/jvms.66.483
|View full text |Cite
|
Sign up to set email alerts
|

Field Efficacy of Recombinant R7 Vaccine against Chicken Leucocytozoonosis

Abstract: ABSTRACT. Effectiveness of vaccine that used recombinant R7 protein (rR7) as antigen that is derived from second-generation schizont (2GS) of Leucocytozoon caulleryi was verified under a field condition against chicken leucocytozoonosis. Chickens reared in a poultry farm where the chickens are attacked by leucocytozoonosis in every year were inoculated with oil-adjuvanted rR7 vaccine (O-rR7), and the immunized chickens were found to have production of antibodies against 2GS at a high level by one shot. Leucocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…It has been reported that the AGP test can be used as diagnostic method for detection of SSA from 10 to 13 days after infection (Morii, 1972(Morii, , 1974(Morii, , 1978. However, as we have shown previously, it is very difficult to detect SSA in the serum of infected chickens in the field (Ito & Gotanda, 2004). The rR7 antigen used in this study is derived from a gene for an outer membrane protein of 2GS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that the AGP test can be used as diagnostic method for detection of SSA from 10 to 13 days after infection (Morii, 1972(Morii, , 1974(Morii, , 1978. However, as we have shown previously, it is very difficult to detect SSA in the serum of infected chickens in the field (Ito & Gotanda, 2004). The rR7 antigen used in this study is derived from a gene for an outer membrane protein of 2GS.…”
Section: Discussionmentioning
confidence: 95%
“…The AGP test is the only assay available commercially and it is widely used in Japan, but has a low sensitivity and is relatively slow. In addition, antibody induced by the vaccine based on oil-adjuvanted recombinant R7 (rR7) protein, which is used to control leucocytozoonosis in Japan, cannot be detected using the AGP test (Itoh & Gotanda, 2002, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its potentially severe impact on poultry production, research on Leucocytozoon in Japan has mainly focused on L. caulleryi infection in domestic chickens, with the objectives to develop protective immunity and vaccinations for the pathogen [14,15]. Leucocytozoon infection has been reported among wild birds of Japan [9,17], however, no classification and genetic analyses of detected Leucocytozoon sp.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a subunit vaccine (leucocytozoonosis vaccine ''Hokken'' [LV]) against this disease using Escherichia coli-expressed immunogenic recombinant R7 (rR7) antigen derived from the outer membrane of the second-generation schizont (2GS) of L. caulleryi (Itoh & Gotanda, 2002). This vaccine is already in use in Japan (Ito & Gotanda, 2004). The molecular structure of rR7 antigen is similar to that of candidate vaccine recombinant antigen of malaria parasites, which are closely related to L. caulleryi taxonomically, especially the circum sporozoite protein of Plasmodium vivax (Zavala et al, 1983).…”
Section: Introductionmentioning
confidence: 99%